Particle fluxes and tides near the continental ice edge on the eastern Weddell Sea shelf - Isla, Enrique; Gerdes, Dieter; Palanques, Albert; Gili, Josep Maria; Arntz, Wolf E. (Deep Sea Research Part II: Topical Studies in Oceanography, 2006)
Special issue EASIZ: Ecology of the Antarctic Sea Ice Zone. Ecology of the Antarctic Sea Ice Zone: Final Symposium.-- 9 pages, 4 figures A short-term experiment to detect the influence of tides on particle fluxes and resuspension of sediment near the sea floor was performed on the eastern Weddell Sea shelf during the expedition ANT XXI/2 on board R/V Polarstern. Two mooring arrays, M1 and M2, equipped with sediment traps and current meters were deployed at 407 and 481 m depth, respectively. The sediment traps and current meters monitored particle fluxes and currents 23 and 8 m above the bottom (mab) for 30 d during the austral spring and summer of 2003–2004. Mooring M1 had an additional sediment trap at 228 mab. At this site the average total mass flux (TMF) to mid-depth was 127 and 313 mg m−2 d−1 close to the sea floor, whereas at site M2 it was 84 mg m−2 d−1. Average current velocities were 7.7 and 9.5 cm s−1 at sites M1 and M2, respectively. The 2-fold increase with depth in the average TMF at site M1 made evident the lateral input of resuspended particles. Current velocity and direction profiles showed a typical diurnal tide pattern with an overlaying 14-d spring-tide period. At both sites the total mass flux and current velocity patterns revealed that settling into the sediment traps is more intense during neap tides. Tides at the eastern Weddell Sea appear as the most important control on resuspension and distribution of shelf sediments. The short duration of the experiment allowed distinguishing intense particle flux pulses, which persisted over the lateral addition of resuspended sediment close to the seabed and indicate that the transfer of matter to the sea floor occurs in intermittent and sudden events Peer reviewed